Respuesta :
Answer: x = 2
y = - 3
Step-by-step explanation:
The system of simultaneous linear equations is expressed as
2x-3y=13- - - - - - - - - - - - - -1
x+2y=-4 - - - - - - - - - - - - -- -2
We would eliminate x by multiplying equation 1 by 1 and equation 2 by 2. It becomes
2x - 3y = 13 - - - - - - - - - - - - - 3
2x + 4y = - 8 - - - - - - - - - - - - - 4
Subtracting equation 4 from equation 3, it becomes
- 3y - 4y = 13 - - 8
- 7y = 21
Dividing the left hand side and the right hand side of the equation by
- 7, it becomes
- 7y/- 7 = 21/-7
y = - 3
Substituting y = - 3 into equation 2, it becomes
x + 2 × - 3 = - 4
x - 6 = - 4
Adding 6 to the left hand side and the right hand side of the equation, it becomes
x - 6 + 6 = - 4 + 6
x = 2
Answer:x=2 , y=-3
Step-by-step explanation:
Using elimination methods
2x-3y=13 equation 1 *1
+2y=-4 equation 2*2
2x-3y=13 equation 1
2x+4y=-8 equation 2
_______
-7y=21
Y=21/-7
Y=-3
Substitute y= -3 in equation 2
X+2(-3)=-4
X-6=-4
X=-4+6
X=2